2, 4, 6-Trichlorophenol (TCP) removal from aqueous solution using Canna indica L.: kinetic, isotherm and Thermodynamic studies. Issue 1 (2nd January 2021) - Enyoh, Christian Ebere; Isiuku, Beniah Obinna
ABSTRACT: The study evaluated the effectiveness of an aquatic plant, Canna indica to remove 2, 4, 6-Trichlorophenol (TCP) from aqueous solution in a hydroponic set-up. The effects of TCP initial concentration (50–250 mg/L) and solution pH (4–9) on TCP biosorption were investigated. The removal efficiency increased with days and initial concentrations. The optimum removal was obtained at pH 4.0. The equilibrium data obtained were analysed by Langmuir, Freundlich, Temkin, Elovich and Dubinin-Radushkevich isotherm models. The equilibrium time was found to be 20 days. The Langmuir and Freundlich model gave the best correlation with the experimental data. According to Langmuir model, the maximum monolayer biosorption capacity of C. indica for TCP was found to be 52.08 mg/g, at 25 ± 2°C. The adsorption was found to follow the pseudo-first-order kinetics. The intraparticle diffusion model revealed that intraparticle diffusion is not the sole rate-limiting step for the biosorption process. Thermodynamic parameter such as standard free energy (Δ G o ) was −2537.697 kJ/mol. This showed that the biosorption process was highly spontaneous and proceeded mainly by chemisorption process. C. indica used in this study is eco-friendly, widely available and offers greater potential for wastewater treatment for removal of chlorinated pollutants such as TCP from aqueous solutions.